The Models of Supporting the Strategic Decisions on Engineering Products Competitiveness; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Tceplit A. P. (Industrial Engineering and Environmental Research, 2015)
Title screen